Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.jmedchem.3c00545
|View full text |Cite
|
Sign up to set email alerts
|

Prodrug Strategies for the Development of β-l-5-((E)-2-Bromovinyl)-1-((2S,4S)-2-(hydroxymethyl)-1,3-(dioxolane-4-yl))uracil (l-BHDU) against Varicella Zoster Virus (VZV)

Abstract: Varicella zoster virus (VZV) establishes lifelong infection after primary disease and can reactivate. Several drugs are approved to treat VZV diseases, but new antivirals with greater potency are needed. Previously, we identified), which had significant anti-VZV activity. In this communication, we report the synthesis and evaluation of numerous L-BHDU prodrugs: amino acid esters (14−26), phosphoramidates (33−34), long-chain lipids (ODE-L-BHDU-MP, 38, and HDP-L-BHDU-MP, 39), and phosphate ester prodrugs (POM-L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(110 reference statements)
0
0
0
Order By: Relevance
“… 26 Next, coupling of l -BHDU ( 17 ) was performed with POM chloride ( 23 ) in the presence of N -methyl imidazole in THF to furnish POM- l -BHDU-MP ( 24 ) in 55% yield ( Scheme 5 ). 16 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 26 Next, coupling of l -BHDU ( 17 ) was performed with POM chloride ( 23 ) in the presence of N -methyl imidazole in THF to furnish POM- l -BHDU-MP ( 24 ) in 55% yield ( Scheme 5 ). 16 …”
Section: Resultsmentioning
confidence: 99%
“…18 The pharmacokinetic studies revealed that POM- l -BHDU-MP had a better oral absorption profile compared to l -BHDU. 16 Repeated assay in humanized mice showed that POM- l -BHDU-MP was effective when administered orally once per day at 11.3 mg/kg or higher, which indicates its potency and bioavailability in vivo. 18 POM- l -BHDU-MP was evaluated as a topical treatment for VZV and HSV in a human skin explant model, which demonstrated highly effective antiviral activities against both viruses at 0.2% formulated in cocoa butter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These prodrugs are metabolized to their respective monophosphates by esterases, demonstrating an improved bioavailability. In recent studies, the improvement of the pharmacokinetic properties through the development of dipivoxil-and disoproxilmasked monophosphates was shown [112]. However, this type of prodrug has a significant drawback; upon their hydrolysis by esterases, the toxic formaldehyde is produced as a byproduct, making this approach less promising for further development [113].…”
Section: Phosphonates and Pom/poc-masked Prodrugsmentioning
confidence: 99%